Correlation Between Interpersonal Communication Dimensions and Anti-Liquor Campaign Strategies - Nelci Batlolona; Rachmat Kriyantono; Reza Safitri (Sekolah Pascasarjana Universitas Brawijaya, 2020)
Liquors are one element that make up a major category of Narcotics, Alcohol, Psychotropics and Addictive Substances (NAPZA in Indonesian abbreviation). Addiction to liquors can cause mental disorders that may corrupt reasoning, sensing and behavioral functions (Dadang, 2005). Malang City Resort Police Department has conducted a campaign titled with â€œSocialization of Impacts, Juridical Aspects, and Mitigation of NAPZAâ€ to influence public attitudes and awareness. Interpersonal communication worked by coordinator (mentor) on Maluku students, which is done by focusing on dimensions of openness, positiveness, empathy, supportiveness and equality,has providedMaluku students with knowledge about liquors and also prevent them from building habits of consuming liquors. The purpose of this study is to the correlation between interpersonal communication dimensions and anti-liquor campaign strategies toward Maluku students in Malang City. Research type is a correlation (relationship) study with quantitative approach. There are two variables in this research, namely, Interpersonal Communication Dimensions (X) and Anti-Liquor Campaign Strategies(Y). Sample size is 62 Maluku students who join at Forum Mahasiswa Maluku Bersatu (FMMB). Data were directly obtained from respondents with questionnaire. Hypothesis was tested using Spearmanâ€™s correlation coefficient assisted with SPSS Version 23 for Windows. Result of research shows that interpersonal communication dimensions have positive relationship, but in low category, with anti-liquor campaign strategies toward Maluku students in Malang City.